A non-radioactive assay for precise determination of intracellular levels of imatinib and its main metabolite in Bcr-Abl positive cells - Mlejnek, Petr; Novak, Ondrej; Dolezel, Petr (Talanta, 2011)
Multidrug resistance (MDR) is often associated with overexpression of the P-glycoprotein (P-gp, ABCB1). It was demonstrated that the P-gp mediated efflux decreases the drug concentration in cancer cells which results in the failure of chemotherapy. However, the MDR phenotype in cancer cells obviously involves various mechanisms. Therefore, if we want to estimate a contribution of the P-gp expression to the MDR phenotype, a clear quantitative relationship between the intracellular drug level and cell sensitivity must be established. To achieve this goal, a sensitive and non-radioactive assay for precise determination of intracellular levels of imatinib and its main metabolite N-desmethyl imatinib (CGP 74588) has been developed. The assay is based on an optimised extraction of cells with 4% formic acid after their separation from the growth medium by centrifugation through a layer of silicone oil. Cell extracts are subsequently analyzed by LC/MS/MS. Calibration curves were linear from 1 to 500 nmol/l for imatinib and from 2 to 500 nmol/l for CGP 74588, with correlation coefficients (r(2)) better than 0.998 and 0.996, respectively. The limit of quantitation (LOQ) was 1 nmol/l for imatinib and 2 nmol/l for CGP 74588. Our method has been successfully applied to the determination of intracellular levels of imatinib in sensitive K562 and their resistant variant, K562/Dox cells.
Keywords: chronická myeloidní leukemie; imatinib mesylát; plynová chromatografie s hmotnostně spektrometrickou detekcí; Humans; Antineoplastic Agents; Piperazines; Pyrimidines; protinádorové látky; piperaziny; Imatinib Mesylate; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; biotest; Biological Assay; Gas Chromatography-Mass Spectrometry; pyrimidiny; Benzamides; benzamidy; lidé; Limit of Detection; limita detekce; buňky K562; K562 Cells